Well-Log-Based Analysis of Pore Pressure and Minimum Effective Stress (Fracture Gradient) in the Penobscot B-41 Well, Offshore Nova Scotia: Well-Log-Based Analysis of Pore Pressure and Minimum Effective Stress (Fracture Gradient) in the Penobscot B-41 Well, Offshore Nova Scotia - Henri Jeni Tua Baringin Sitohang (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study analyzes pore pressure () and minimum effective stress (fracture gradient) in the Penobscot Offshore Field using well log data from wells Penobscot B-41. The Eaton and Bowers methods were applied to estimate pore pressure and minimum effective stress (fracture gradient), while vertical stress () and minimum horizontal stress () were calculated from density data. The results indicate the presence of a top overpressure zone beginning at approximately 8,376 ftTVD, marked by a significant deviation from the normal compaction trend. A reversal depth is also identified around 9,000-9,200 ftTVD, indicating a shift in the overpressure mechanism from normal compaction to unloading. Pore pressure values derived from both Eaton and Bowers methods show overall consistency, although Bowers tends to yield more conservative estimates in the deeper sections. Unloading is particularly evident in the deeper interval of well Penobscot B-41, where elevated values are observed without corresponding low density, suggesting stress release caused by fracturing or fluid migration. Effective stress () calculations reveal high-risk zones for fracturing at depths greater than 9,500 ftTVD, which should be carefully addressed in mud weight design. Overall, the integration of Eaton and Bowers methods with effective stress evaluation successfully characterizes the geopressured system of the Penobscot Field. These findings provide an essential basis for drilling risk mitigation and casing design optimization. Keywords: Pore Pressure; Fracture Gradient; Normal Compaction Trend (NCT); Eaton’s Method; Bowers Velocity Model; Penobscot Field